Artificial Intelligence and Acupuncture: A Manifesto. - Menéndez Covelo, Vanessa (Journal of Chinese Medicine (JCM), 2025)
This article explores the current applications of artificial intelligence (AI) to the practice of acupuncture, and attempts to foresee how this might change the way acupuncturists practise. Sample uses of a specialised acupuncture application of the large language model ChatGPT are given, in which brief handwritten notes are uploaded and diagnosis and treatment are provided by the 'AI assistant'. The article concludes by considering the advantages and pitfalls presented to the acupuncture profession by AI.